Upaya Memaksimalkan Kesehatan Lansia Di Desa Iroyudan Dengan Menggunakan Metode FHCWSAE (For Health Check With Socialization And Education) - Dena Munarsih; Debby Vitara; Husnul Khatimah; Haka R Pratama; Aditya Mandala Pratama (Bangun Desa: Jurnal Pengabdian Masyarakat, 2022)
Elderly is an age group that is very vulnerable to experiencing health problems. The method used is an observational approach. The analysis carried out focuses on processing numerical data which is interpreted with health phenomena in the village community. The analysis resulted in problem solving in the form of consultations, health checks, and training in the health sector. Some of the programs that the team carried out were counseling on self-medication and health checks for the elderly. With this problem solving method, it is hoped that it can help solve the health problems of the elderly in Iroyudan Village. To be able to face life, the elderly must maintain good health and fitness, the elderly must carry out regular sports activities, carry out a healthy lifestyle, rest, do not smoke and have regular health checks. One of the efforts to achieve health is by exercising so that for the elderly to be able to get a healthy body, one of them must regularly do sports activities. Regular exercise is an effective and safe alternative to improve or maintain fitness and health if done properly. Aerobic activities suitable for the elderly include: walking, low impact aerobic exercise, elderly exercise, cycling, swimming and so on. Whether or not an exercise program is useful for the elderly also depends on the program being implemented. Keywords: Elderly, health for the elderly, self-medication counseling